Economic evaluation of finotonlimab plus bevacizumab as first-line therapy for advanced hepatocellular carcinoma - XueYin Xu; Lian Tang; XiangHua Piao; ShaoQing Zhan; Yong Chen; PanFeng Feng (PLoS ONE, 2026)
Objective To compare the cost-effectiveness of dual-agent group (finotonlimab combined with a bevacizumab biosimilar) (SCT510) versus sorafenib as first-line treatment for advanced hepatocellular carcinoma (HCC) from the perspective of the Chinese healthcare system. Methods Based on the results of a Phase III clinical trial, a three-state partitioned survival model was constructed. The primary outcomes of the model included total costs, total quality-adjusted life years (QALYs), and the incremental cost-effectiveness ratio (ICER). Cost-effectiveness analysis was employed to evaluate the economic efficiency of the dual-agent group compared to the sorafenib group as first-line treatment for advanced HCC. The model cycle length was set at 3 weeks, with a time horizon of 10 years and a discount rate of 4.5%. The willingness-to-pay (WTP) threshold was set at three times China’s 2025 per capita gross domestic product (GDP) (299,400 CNY). One-way sensitivity analysis and probabilistic sensitivity analysis were conducted to assess the robustness of the results. Results The ICER for the dual-agent group compared to the sorafenib group, calculated based on QALYs, was 859,053.76 CNY/QALY, which is higher than the WTP threshold (299,400 CNY). One-way sensitivity analysis indicated that parameters such as utility value in the PD state, utility value in the PFS state, the cost of finotonlimab and bevacizumab biosimilar had a significant impact on the ICER, while other parameters had minimal influence. The base-case analysis results were robust. Probabilistic sensitivity analysis showed that at a WTP threshold of 299,400 CNY, the probability of the dual-agent group being cost-effective was 0%. When the WTP threshold was approximately 842,000 CNY, the two groups had equal probability of being cost-effective. The probabilistic sensitivity analysis results were consistent with the base-case analysis. Conclusion From the perspective of the Chinese healthcare system, finotonlimab combined with a bevacizumab biosimilar is not cost-effective as first-line treatment for advanced HCC.